Large shareholder trading and the complexity of corporate investments - Goldman, Eitan; Strobl, Günter (Journal of Financial Intermediation, 2013)
This paper investigates how the presence of a large institutional shareholder affects the complexity of corporate investments. Our analysis is based on the observation that the blockholder’s planning horizon does not necessarily coincide with the time it takes for the market to correctly evaluate these investments. It demonstrates that this horizon mismatch creates an incentive for the large shareholder to manipulate the firm’s stock price. In equilibrium, corporate managers respond to these manipulation attempts by increasing the complexity of their investments. This in turn lowers the large shareholder’s incentive to collect costly information, which reduces price informativeness and exacerbates managerial myopia. Thus, our analysis identifies a new cost of block ownership resulting from an increased complexity of corporate investments.